2016
DOI: 10.5001/omj.2016.06
|View full text |Cite
|
Sign up to set email alerts
|

From Symptoms to Diagnosis: An Observational Study of the Journey of Rheumatoid Arthritis Patients in Saudi Arabia

Abstract: Failure of patients to be seen by rheumatologists at RA onset delayed diagnosis and treatment. Thus, RA diagnosis can be accelerated by encouraging early referral to rheumatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 23 publications
3
47
2
Order By: Relevance
“…Previous studies conducted in other Brazilian cities showed a diagnostic time of approximately 8 [17], 12 [18] and 39 months [9], showing that the present study is within the national intervals, and presented similarity to a study in Brasília, whose time was 27 months [19]. The international literature offers a variety of data, such as a mean time of 6 months in European countries [20], 30 months in Saudi Arabia [7] and up to 33 months in Colombia [21]. These data show that there are contributing factors for the diagnostic time that differ according to locality.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies conducted in other Brazilian cities showed a diagnostic time of approximately 8 [17], 12 [18] and 39 months [9], showing that the present study is within the national intervals, and presented similarity to a study in Brasília, whose time was 27 months [19]. The international literature offers a variety of data, such as a mean time of 6 months in European countries [20], 30 months in Saudi Arabia [7] and up to 33 months in Colombia [21]. These data show that there are contributing factors for the diagnostic time that differ according to locality.…”
Section: Discussionsupporting
confidence: 82%
“…Despite this, the world reality differs from that recommended. In Saudi Arabia, an average time of approximately 30 months was verified [7], whereas in England, the ERAN study found a period of approximately 4 months for the diagnosis [8]. In Brazil, a study from São Paulo verified that the average waiting time between the beginning of the symptoms and rheumatologic evaluation was on average 39 months .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed in Saudi Arabia found that patients consulted an average of 4 physicians between their first symptom of RA and final diagnosis, with a mean time from the first physician visit to final RA diagnosis of ~30 months. 14 Although patients consulted with physicians at a mean of 7 months after the onset of RA symptoms, very few subjects initially sought a consultation with rheumatologists, who were ultimately responsible for diagnosing most RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…The time between symptom onset and diagnosis of rheumatoid arthritis by a rheumatologist in Saudi Arabia has been reported to be as high as 30 months 16. In comparison, a French study calculated an average of 53 days between PCP visit and rheumatologist assessment 17.…”
Section: Discussionmentioning
confidence: 99%